2023
DOI: 10.1111/raq.12795
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment and anti‐Vibrio activity of essential oils: Potential for application in shrimp aquaculture

Abstract: This present paper aimed to review the past 4 years (2019–2022), the inhibition of Vibrio spp. (including Vibrio's causing AHPND) by EOs, as well as the potential toxicity of the EOs towards crustaceans, with an emphasis on Artemia spp. In the present review, 27 EOs from terrestrial plants are reported regarding their anti‐Vibrio activity. Among these 27 studies, Salvia officinalis and Thymus vulgaris (Lamiaceae family) were found to be the most numerous. Among the Vibrio spp., V. parahaemolyticus (non‐AHPND s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 117 publications
0
0
0
Order By: Relevance
“…The utilization of citral as feed supplement in aquaculture has not been widely used, and the effect against organism thought to be influenced by the dose (Zheng & Bossier, 2023). A previous study by Mori et al (2019) reported that citral has been used as raw material addition in common snook (Centropomus undecimalis) fish feed by dose of 440 mg-1760 mg/kg feed.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of citral as feed supplement in aquaculture has not been widely used, and the effect against organism thought to be influenced by the dose (Zheng & Bossier, 2023). A previous study by Mori et al (2019) reported that citral has been used as raw material addition in common snook (Centropomus undecimalis) fish feed by dose of 440 mg-1760 mg/kg feed.…”
Section: Introductionmentioning
confidence: 99%